The Development of Financial Management Teaching Materials with Assure Model - Fatmawarni M.M (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
This study aims to develop financial management teaching materials with Assure model. The phenomenon that occurs in this study is the lack of students’ ability in understanding financial management and the lack of students’ independence in learning and lack of availability in teaching materials of learning financial management. Based on the study results, students of accounting education in fourth semester are 96 people consisting of 10 men and 86 women. From 96 students, it is viewed from the parents' income that 39.58% of parents’ income is between 2 million to 2.99 million, 32.29% parents’ income is 1 million to 1.99 million and the rest is that the students’ income is above 3 million. If it is seen from the initial ability of accounting education students in the subject of financial management, it is still in low category, this is because the student has never been familiar with financial management learning, and if it is viewed from the student learning style that the student's visual learning style tends in using learning media, based on study result of 66.67% student very agree in study using media, 15.62% student strongly agree to hear friends’ explanation and 7.29% student strongly agree learning is done with concept map. If it seen from the auditory learning style, the student is more inclined to the learning which is done with the discussion, that is 35.42% and the learning which is done with music is to 19.79%, while the students who strongly agree with game are 16.67%. And in terms of kinesthetic learning style more students who tend to study at the field are 34.38%. Based on the results of questionnaires that are distributed to students based on characteristics, then it is developed teaching materials of financial management, among others, the development of Assure learning model that refers to the learning strategy by applying some learning models include Project Based Learning model, Discussion and Inquiry, Problem based Learning, and developing learning media